Effect of chromium and copper stress on antibiotic resistance genes transfer and associated metabolic mechanism in electrochemical system treating sulfanilamide wastewater. Issue 1 (February 2023) - Zhang, Ke; Guo, Jingyue; Luo, Hongbing; Chen, Wei; Chen, Jia; Mo, You; Zou, Zuyin
Abstract: To investigate the electrochemical process and metabolic mechanism of sulfonamide wastewater treatment under chromium and copper stress in bioelectrochemical system, electron transfer and antibiotic resistance genes (ARGs) transfer were investigated. Metagenomics was used to reveal metabolic pathways, antibiotic resistance mechanisms, carbohydrate active enzymes, etc. The results indicated that copper stress not only did not affect the electricity production performance of the electrochemical system, but also promoted the electron transfer efficiency. Copper stress can also effectively control ARGs and mobile genetic elements (MGEs). The metagenomics analysis showed that Cu increased the abundance of coxA and cox1 genes in the electrochemical system and increased the C-type cytochrome, thereby improving the ability of electron transfer. In contrast, chromium stress affected electrochemical system performance and accelerated ARGs transfer, and increasing the risk of resistance gene horizontal transfer. The mechanism of antibiotic resistance was mainly through the efflux function of antibiotics (61.5%), which was mainly related to Proteobacteria (51.5%) and Firmicutes (25.4%). The results also indicated that the glycolysis process was promoted by Cu, while the process was negatively affected by Cr. This study revealed the effect of chromium and copper stress on the metabolic mechanisms of microorganisms in bioelectrochemical system at the genetic level and provided a theoretical basis for risk control of livestock and poultry wastewater. Graphical Abstract: ga1 Highlights: The mechanism of antibiotic removal under Cu - Cr stress was revealed. Cu is beneficial for the control of mobile genetic elements (MGEs) transfer. Chromium inhibited carbohydrate metabolism by inhibiting enzymes (GH94, GH36). Cu increased coxA, cox1, C cytochrome, and improved electron transport capacity. The co-selection mechanism of heavy metals and antibiotics was elucidated.